Recurrent paediatric ependymoma: a multicentre analysis of clinical features and tumour biology in the molecular era - Ritzmann, Timothy (2018)
Introduction: Ependymoma is the second most common malignant brain tumour of childhood. 50% of children with primary disease recur; three-quarters of these do not achieve long term survival. In the ‘molecular era’ of cancer research, diagnosis combines advanced molecular profiling with histopathological assessment. Whilst primary ependymomas can be classified based on epigenetic and transcriptomic features, there is little information on molecular signatures at recurrence. However, some small studies have implicated cancer immunity. Trials of novel therapies at recurrence have been disappointing. This study undertook molecular profiling of recurrent ependymoma, combined with contemporary clinical data, to better understand recurrence biology and potential therapy options. Methods: Clinical outcomes for 188 children with recurrent ependymoma were analysed. Cases with primary and matched recurrent samples were included in DNA methylation (n=56), RNA sequencing (n=52) and immunohistochemical (IHC) (n=56) analyses. RNA sequencing from FFPE tissue was validated to expand the cohort. Results: Recurrence was the strongest predictor of long term survival. Treatment approach at primary diagnosis was not associated with survival, but radiotherapy at first recurrence was associated with better short-term outcomes. Children with the commonest DNA methylation based diagnoses, EPN_PFA and EPN_RELA, had equally poor outcomes. RNA sequencing from FFPE tissue was effective, therefore tumours sequenced from FFPE and FF tissue were included in paired gene expression analyses. Transcriptomic and DNA methylation analyses identified three similar subgroups in FFPE and FF cohorts (PF1, PF2 and ST). At first recurrence, PF1 was associated with downregulated immune and inflammatory ontologies, which may indicate tumour immune escape. PF2 and ST subgroups demonstrated upregulation of ontologies associated with adaptive immunity. Despite this, there was little evidence of change in either immunogenicity or T-cell effector activity at first recurrence. IHC analysis identified a fall in inflammatory cells in posterior fossa tumours at recurrence and indicated that ependymoma is an immune excluded tumour. Conclusions: This study highlights both the abysmal prognosis for this disease, and the need for a better understanding of tumour biology to improve outcomes. This study has contributed novel data on changes at recurrence across molecular subgroups, and identified the immune excluded nature of ependymoma, which may be important in guiding therapy. The validation of RNA-seq from FFPE in childhood brain tumours has facilitated access to a large set of previously uninvestigated samples.